2017
DOI: 10.1089/thy.2016.0456
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hepatic TRβ Protein Expression, Lipogenic Gene Expression, and Long-Chain Acylcarnitine Levels During Chronic Hyperthyroidism and Triiodothyronine Withdrawal in a Mouse Model

Abstract: Background: Thyroid hormone (TH) has important roles in regulating hepatic metabolism. It was previously reported that most hepatic genes activated by a single triiodothyronine (T3) injection became desensitized after multiple injections, and that approximately 10% of target genes did not return to basal expression levels after T3 withdrawal, despite normalization of serum TH and thyrotropin (TSH) levels. To determine the possible mechanism(s) for desensitization and incomplete recovery of hepatic target gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In the present study, fluoride treatment could significantly upregulate TRβ mRNA and significantly downregulate TRα expression on 41.9 and 62.7 mg/L groups. Although numerous studies have determined that the expression TRβ gene was induced by T3 (Fini et al, ; Hinther et al, ; Liu et al, ), Ohba et al () found that T3 treatment decreased the expression TRβ gene in mouse. In addition, TRα knockdown caused an increase expression of TRβ mRNA in Xenopus tropicalis tadpoles (Wen and Shi, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, fluoride treatment could significantly upregulate TRβ mRNA and significantly downregulate TRα expression on 41.9 and 62.7 mg/L groups. Although numerous studies have determined that the expression TRβ gene was induced by T3 (Fini et al, ; Hinther et al, ; Liu et al, ), Ohba et al () found that T3 treatment decreased the expression TRβ gene in mouse. In addition, TRα knockdown caused an increase expression of TRβ mRNA in Xenopus tropicalis tadpoles (Wen and Shi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, different chromatin modifications of target genes could play an important role in regulating transcription during acute and chronic thyroid hormone treatments. We have also reported that thyroid hormones reduce hepatic TRβ protein expression in a time-dependent manner [ 35 ]. Taken together, time-dependent changes in transcriptional mechanisms may partly explain the hysteresis of thyroid hormone-responsive genes.…”
Section: Pathophysiology Of Istmentioning
confidence: 99%
“…Thus, the TH regulation of transcription may be more complex than originally thought and may undergo temporal changes depending upon its ability to express secondary transcriptional regulators in addition to its own direct transcriptional regulation. In this connection, it is noteworthy that more than 90% of the hepatic genes that were positively- or negatively-regulated by TH were different in mice injected daily with T 3 for 10 days than those seen in mice only 6 hours after one injection with T 3 [ 21 , 77 ]. These findings suggested that there may be a secondary induction of other transcription factors that regulated the transcription of downstream target genes.…”
Section: New Mechanisms Of Transcriptional Regulation By Thmentioning
confidence: 99%